TRAINING E-COMMERCE USING WOOCOMMERCE FOR SENIOR HIGH SCHOOLS IN TANGERANG REGENCY - Hajar, Dewi; Ari, Aloysius (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2023)
Along with the rise of e-commerce, digital literacy is very necessary not only for IT professionals, but also for all business people. Knowledge of technology is very necessary for business people so that their business can be increasingly recognized by the wider community. WordPress has become one of the most popular websites in the world. 43% of websites on the Internet are currently powered by WordPress. Woocommerce is one of WordPress's extension that focuses on e-commerce. WooCommerce is easy to learn for everyone, including students who don't have any technological knowledge. The training program was conducted by two lecturers from the e-commerce logistics study program, with five students as instructors. There are 90 participants from 4 senior high schools. After the training, there are nine questions for the evaluation of the participant. More than 92% of the questions were answered correctly by the participants. There are two questions that were answered 100% correctly. Therefore, the training was successful in making all participants understand how to create Woo commerce for selling their products.